Distribution of basement membrane antigens in clinical gastric adenocarcinomas: an immunohistochemical study. Issue 12 (December 1987) - Nakamura, K; Mori, M; Enjoji, M
Abstract : The distribution of laminin and collagen type IV in the basement membranes of 85 gastric adenocarcinomas was studied using immunoperoxidase techniques to check for invasive carcinoma. Lymph nodes with metastases were also studied in 23 cases. Thick and discontinuous staining of the basement membranes was observed in 12 cases of well differentiated adenocarcinoma; thin and discontinuous staining in 26 (12 well and 14 moderately differentiated adenocarcinomas); fragmentary staining in 36 (15 moderately and 21 poorly differentiated adenocarcinomas); and unrecognisable basement membrane staining in the remaining 11 cases of poorly differentiated adenocarcinoma. These patterns were largely related to the histological grade, the nuclear atypism and loss of polarity of tumour cells, and the degree of inflammatory infiltration.